„Mała ojczyzna” w świadomości Ukraińców przesiedlonych z Polski po II wojnie światowej - Hałyna Bodnar (Ksiegarnia Akademicka Publishing, 2021)
The “Little Homeland” in the consciousness of the Ukrainian citizens displaced from Poland after the Second World War